Isonicotinamide-Stabilized Gold Nanoclusters as Fluorescent Probes for the Determination of 2, 4, 6-Trinitrophenol. (13th April 2022) - Zeng, Chao; Xie, Chenxia; Zhang, Min; Cao, Chengdu; Guo, Luohua; Wang, Miao; Zhuang, Qianfen; Wang, Yong
Abstract: Water-soluble isonicotinamide-stabilized fluorescent gold nanoclusters (AuNCs) were synthesized in one step and used as fluorescent probes for the sensitive and selective determination of 2, 4, 6-trinitrophenol (TNP). The AuNCs were characterized by transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and fluorescence spectroscopy. The fluorescence of the isonicotinamide-stabilized AuNCs was quenched by TNP that follows a linear relationship with the TNP concentration from 0.2 to 20 µM. The sensor provides a low detection limit of 0.06 µM. By using absorption spectroscopy, fluorescence spectroscopy and fluorescence lifetime, the fluorescence quenching mechanism was demonstrated to be due to the inner filter effect between AuNCs and TNP. The sensor was successfully employed for TNP determination in water samples.